Legitimating the use of force in international politics: Kosovo, Iraq and the ethics of intervention - Bjola, C (Routledge, 2010)
This research monograph provides a provocative answer to the intensely contested question regarding the conditions under which the decision to use force can be reckoned as legitimate in international relations. The book argues the concept of 'deliberative legitimacy', understood as the non-coerced commitment of an actor to abide by a decision reached through a process of communicative action, offers the most appropriate framework for addressing this question. The theoretical originality and empirical value of the concept of deliberative legitimacy comes fully into force with the examination of two of the most severe international crises from the post Cold War period: the 1999 NATO intervention in Kosovo and the 2003 US military action against Iraq.